2019
DOI: 10.1111/aos.14047
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of primary retinitis pigmentosa patients using colour Doppler flow imaging and optical coherence tomography angiography

Abstract: Purpose To find the potential relation between changes in retinal large vessels and terminal vessels using colour Doppler flow imaging (CDFI) and optical coherence tomography angiography (OCTA) and to compare the respective advantages of CDFI and OCTA in evaluating vascular changes in retinitis pigmentosa (RP) patients. Methods A prospective series of case study was conducted to enrol RP patients and age‐matched controls, who were, respectively, imaged by CDFI and OCTA. Repeatability and reproducibility of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
0
25
0
2
Order By: Relevance
“…Significant associations between visual acuity and parafoveal flow density in the superficial [29,32] and deep retinal layer [31,32], foveal flow density in the superficial retinal layer [32,35], and superficial FAZ [31,32,35] have also been reported. Correlations between superficial and deep capillary plexus vessel densities with multifocal electroretinogram values and ganglion cell complex layer thickness have also been shown [30].…”
Section: Octa In Retinitis Pigmentosamentioning
confidence: 95%
See 2 more Smart Citations
“…Significant associations between visual acuity and parafoveal flow density in the superficial [29,32] and deep retinal layer [31,32], foveal flow density in the superficial retinal layer [32,35], and superficial FAZ [31,32,35] have also been reported. Correlations between superficial and deep capillary plexus vessel densities with multifocal electroretinogram values and ganglion cell complex layer thickness have also been shown [30].…”
Section: Octa In Retinitis Pigmentosamentioning
confidence: 95%
“…Takagi et al examined flow area in both the superficial and deep capillary plexus and similarly showed that these parameters were lower in RP eyes vs. controls [34]. Wang and colleagues examined the foveal and parafoveal subfields and found that the vessel area densities in the superficial capillary plexus in all subfields in RP eyes were lower than in control eyes [35].…”
Section: Octa In Retinitis Pigmentosamentioning
confidence: 99%
See 1 more Smart Citation
“…The shape and distribution of neovascularization in tumors are related to the aggressive growth pattern of cancer cells, which is helpful to distinguish the nature of the tumor [5]. Color Doppler flow imaging (CDFI) is often used to show the blood flow inside the tumor, but CDFI can provide limited data in some low-velocity microvessels [6]. As a novel US technique, Superb Microvascular Imaging (SMI) can quickly, simply and noninvasively study the microvascular distribution in the tumor and evaluate the microvascular perfusion [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are some differences between benign and malignant thyroid nodules in blood ow pattern and vascular morphology, which is helpful to distinguish benign and malignant thyroid nodules [6]. Color Doppler ow imaging (CDFI) is often used to show the blood ow inside the tumor, but CDFI is not good for some low-velocity microvessels [7]. As a novel ultrasonic technique, SMI can quickly, simply and noninvasively observe the microvascular distribution in the tumor and evaluate the microvascular perfusion [8].…”
Section: Introductionmentioning
confidence: 99%